Unusual Presentation of Primary Squamous Cell Carcinoma of Mandible. (19th December 2016) - Shanmugasundaram, Karpagavalli; Subramanian, Sathasiva; Vedam, Vaishnavi; Kumar, Vimal
Abstract : Carcinoma arising primarily from the jaw is a locally aggressive lesion with poor prognosis. Primary intraosseous carcinoma (PIOC) lesion develops either de novo remnants of odontogenic epithelium, odontogenic cyst/tumor, epithelium remnants, or/and salivary gland residues. We describe very interesting case of primary intraosseous carcinoma of mandible. This extensive lesion was sent for oncological opinion and further management. Due to the uncertainty of diagnostic criteria of PIOC, only few cases of this lesion with a typical presentation have been reported. This article presents a case of primary intraosseous carcinoma with a unique appearance and detailed review stating its clinicopathological correlation.